Vegetation Structure and Composition in the Nusa Gede Panjalu Nature Reserve Area, Ciamis, Indonesia - Bahana Aditya Adnan; Giena Sitha Supriatna; Tiktiek Kurniawati (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2023)
The Nusa Gede Panjalu Nature Reserve in Ciamis Regency is a conservation area that holds a variety of biodiversity and within it is a natural tourism area. It is feared that the existence of natural tourism areas will result in damage caused by human activities. This study aims to analyze the structure and composition of vegetation as well as environmental factors that affect vegetation growth in the Nusa Gede Panjalu Nature Reserve area. The method used in this study is the line transect method with sampling using quadrat. The data obtained were analyzed using the Importance Value Index (IVI), the index of Shannon-Wiener, and the index of Evenness. The results showed that the structure and composition of the vegetation in the Nusa Gede Panjalu Nature Reserve consisted of 416 individuals divided into 29 species. The plant species with the highest Importance Value Index (IVI) in the seedling category were Dysoxylum densiflorum (28.73%), the pole category Litsea noronhae (23.72%) and for the tree category Dysoxylum densiflorum (49.12%). The diversity index obtained is included in the moderate level of diversity. Environmental factors affecting the growth of vegetation in the Nusa Gede Nature Reserve are the temperature, humidity, light intensity, and pH with an average temperature of 28.4°C, humidity of 85.1% light intensity of 1070.1 lux, and pH of 6.3.